Blockchain and real estate: Dopo di Noi project. Issue 2 (6th March 2020) - Morena, Marzia; Truppi, Tommaso; Pavesi, Angela Silvia; Cia, Genny; Giannelli, Jacopo; Tavoni, Marco
Abstract : Purpose: This paper aims at investigating the possibility of effectively implementing the blockchain technology in the real estate environment, specifically applied to the Trust legal instrument in Dopo di Noi (After Us) project, which is intended to guarantee assistance to persons with severe disabilities. Design/methodology/approach: The paper is focused on how to apply the blockchain to the tool of Trust, analyzing the main features and characteristics of this technology. Findings: The paper proposes two potential solutions for managing the Trust tool in the real estate sector, specifically within the Dopo di Noi project. The first simpler proposal is based on timestamping application. The second one radically changes the classical Trust model and introduces an automatization level in the process. Social implications: The paper presents potential applications of the blockchain technology within the framework of Dopo di Noi project, which allows among other features, legal and tax facilitation for the institution of Trusts to benefit persons with severe disabilities. Originality/value: This paper highlights the potentiality of the combination of the blockchain technology and the real estate environment and applies the blockchain technology to the Dopo di Noi project. Specifically, with the second solution, the paper proposes a platform that gathers, in a single network, various elements of the blockchain technology, such as timestamping, smart property, smart contract, and links them in order to provide services to persons with severe disabilities.